Multi-objective optimization in surface transformation hardening of S50C carbon steel by single-mode fiber laser - Mohd Radzman, Mohamad Aizat; Ismail, Mohd Idris Shah; Mohd Ariffin, Mohd Khairol Anuar; Tang, Sai Hong; As'arry, Azizan (Malaysian Tribology Society, 2023)
Laser transformation hardening (LTH) process has become a better alternative for manufacturing industries. LTH offers a non-contact method, creating a pristine manufacturing setting and yielding high-quality products efficiently and cost-effectively at a significant scale. In the present work, parametric optimization for laser transformation hardening of JIS S50C medium carbon steel using L27 orthogonal array design of experiments was experimentally investigated. The grey relational analysis (GRA) was utilized by considering multi performance characteristics, namely austenitizing temperature, and hardened depth. The GRA results confirmed that the best combination of process parameters was obtained during laser power 150 W, scanning speed 15 mm/s, and track distance 100 µm. Scanning speed was found to be the process parameter that provides the most significant effect compared to laser power and track distance in obtaining higher austenitizing temperature and greater hardened depth through the response table. The study revealed the multi-performance characteristics can be enhanced by selecting the proper process parameters.